Food Safety Basic Concepts, Recent Issues, and Future Challenges - Selamat, Jinap; Iqbal, Shahzad Zafar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is designed to integrate the basic concepts of food safety with current developments and challenges in food safety and authentication. The first part describes basics of food safety, classification of food toxins, regulation and risk assessment. The second part focuses on particular toxins like mycotoxins, aromatic amines, heavy metals, pesticides, and polycyclic hydrocarbons. Recent developments and improvements in the detection of these contaminants are described. The third part deals with the authenticity and adulteration of food and food products, a topic which affects food trade on a national and international level. .
Part 1: Food Safety -- Chapter 1: Food safety systems -- Chapter 2: Regulations for food toxins -- Part 2: Chemical Food Contaminants -- Chapter 3: Safe food production with minimum and judicious use of pesticides -- Chapter 4: Toxic Elements -- Chapter 5: Heterocyclic amines -- Chapter 6: Mycotoxins in Food and food products; current status -- Part 3: Future Challenges -- Chapter 7: Food Adulteration and Authenticity -- Chapter 8: Climate change and food safety.
Keywords: Food science; Industrial microbiology; Analytical chemistry; Food Science; Industrial Microbiology; Analytical Chemistry